Analisis Tingkat Kepentingan Dan Kepuasan Wisatawan Menggunakan Indikator Destinasi Wisata Unggulan - Manvi, Kurnia Ilahi; Fiza, Adek Kurnia (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
To realize sustainable development, each tourist destination needs to evaluate periodically using appropriate and measurable instruments. Various measurement models of leading tourist destinations have been developed by tourism researchers from all over the world but are not fully suitable for use in developing countries such as Indonesia. This study examines the application of leading tourist destination indicators developed by Vengesayi which are specifically designed for developing countries. The results of this study reveal that Vengesayi's indicators are suitable for application in Indonesia with empirical evidence using tourist areas in West Sumatra. This study then develops a research model which is then suggested for the next research agenda